Evaluating child maltreatment and family violence risk during the COVID‐19 Pandemic: Using a telehealth home visiting program as a conduit to families. Issue 1 (30th December 2021) - Bullinger, Lindsey Rose; Marcus, Stevan; Reuben, Katherine; Whitaker, Daniel; Self‐Brown, Shannon
Abstract: The COVID‐19 pandemic has affected many child maltreatment risk factors and may have affected maltreatment among vulnerable families. We surveyed 258 certified providers of an evidence‐based home visiting program, SafeCare, about their perception of the impact of the pandemic on the families they serve. We examined if the providers perceived an overall change in child maltreatment and family violence risk among the families with young children they served and factors that may have contributed to changes. Regressions estimated the relationship between providers' assessment of families' ability to social distance, emotional struggles, and access to public resources/services with providers' perception of child maltreatment and family violence risk in the home. Findings indicate that 87% of providers believed maltreatment risk had increased during the pandemic. Providers serving families who were unable to social distance due to employment were more likely to report increased supervisory neglect and material neglect among the families they serve. Providers reporting that families were struggling with elevated frustration levels also reported more family conflict and material neglect among the families they serve. Results from this research can inform strategic decision‐making for policies and programs that address the challenges low‐income families with young children face in emergency situations. Resumen: La pandemia del COVID‐19 ha afectado muchos factores de riesgo de maltrato del niño y pudiera haber afectado el maltrato en familias vulnerables. Les preguntamos en una encuesta a 258 proveedores certificados de un programa de visitas a casa con base en la evidencia, SafeCare®, acerca de sus percepciones del impacto de la pandemia en las familias a quienes les ofrecían el servicio. Examinamos si los proveedores percibían un cambio general en el maltrato del niño y el riesgo de violencia familiar en familias con niños pequeños a las que les servían y los factores que pudieran haber contribuido a los cambios. Las regresiones calcularon la relación entre la evaluación de los proveedores acerca de la habilidad de la familia para mantener la distancia social física, los problemas emocionales, así como el acceso a recursos y servicios públicos, con la percepción de los proveedores acerca del maltrato infantil y el riesgo de violencia familiar en la casa. Los resultados indican que el 87 por ciento de los proveedores creía que el riesgo de maltrato había aumentado durante la pandemia. Aquellos proveedores que les servían a familias que no podían mantener la distancia social física debido al empleo, estuvieron más propensas a reportar el aumento en la negligencia de supervisión y la negación de material en las familias a quienes les servían. Los proveedores que reportaron que las familias estaban luchando con elevados niveles de frustración también reportaron más conflicto familiar y negación de material en las familias a las que les servían. Los resultados de esta investigación pueden apoyar la toma de decisiones estratégica para políticas y programas que se enfoquen en los retos que enfrentan las familias de bajos recursos con niños pequeños en situaciones de emergencia. Résumé: La pandémie du COVID‐19 a affecté bien des facteurs de risque de la maltraitance de l'enfant et peut avoir affecté la maltraitance chez les familles vulnérables. Nous avons questionné 258 prestataires certifiés d'un programme de visite à domicile fondé sur des données probantes, SafeCare®, sur leur perception de l'impact de la pandémie sur les familles qu'ils servent. Nous avons examiné si les prestataires ont perçu un changement général de la maltraitance de l'enfant et dans le risque de violence familiale au sein des familles avec les jeunes enfants qu'ils servaient et les facteurs qui ont pu contribuer à ces changements. Des régressions ont estimé la relation entre l'évaluation qu'ont fait les prestataires de la capacité des familles à assurer la distanciation sociale, des difficutés émotionnelles et de l'accès aux resources/services publiques avec la perception des prestataires de la maltraitance de l'enfant et du risque de violence familiale à la maison. Les résultats indiquent que 87 pourcent des prestataires pensaient que le risque de maltraitance avait augmenté durant la pandémie. Les prestataires servant les familles qui ne pouvaient pas assurer la distanciation sociale à cause de leur emploi étaient plus à même de faire état d'une négligence acrue de la supervision et de négligence matérielle chez les familles qu'ils servent. Les prestataires indiquant que les familles faisaient face à des difficultés avec des niveaux de frustration élevés ont aussi fait état de plus de conflit familial et de néglicence matérielle chez les familles qu'ils servent. Les résultats de ces recherches peuvent aider les prises de décision stratégiques pour les politiques et les programmes qui répondent aux défis des familles défavorisées avec de jeunes enfants dans des situations d'urgence. Zusammenfassung: Risikobewertung von Kindesmisshandlung während der COVID‐19‐Pandemie: Ein telemedizinisches Hausbesuchsprogramm als Verbindungskanal zu den Familien Die COVID‐19‐Pandemie wirkt sich auf viele Risikofaktoren für Kindesmisshandlung aus und könnte daher einen Einfluss auf Misshandlungen in vulnerablen Familien haben. Wir befragten 258 zertifizierte Anbieter eines evidenzbasierten Hausbesuchsprogramms SafeCare® zu ihrer Wahrnehmung der Auswirkungen der Pandemie auf die von ihnen betreuten Familien. Wir untersuchten, ob die Anbieter eine allgemeine Veränderung des Risikos von Kindesmisshandlung und familiärer Gewalt unter den von ihnen betreuten Familien mit kleinen Kindern wahrnahmen und welche Faktoren zu den Veränderungen beigetragen haben könnten. Mithilfe von Regressionsanalysen wurden die Zusammenhänge zwischen der Einschätzung der Anbieter hinsichtlich der Fähigkeit der Familien zu sozialer Distanz, emotionalen Schwierigkeiten sowie dem Zugang zu öffentlichen Ressourcen/Dienstleistungen und der Wahrnehmung der Anbieter hinsichtlich des Risikos von Kindesmisshandlung und häuslicher Gewalt berechnet. Die Ergebnisse zeigen, dass 87% der Anbieter der Meinung waren, dass das Misshandlungsrisiko während der Pandemie gestiegen war. Anbieter, die Familien betreuten, die aus beruflichen Gründen keine soziale Distanz einhalten konnten, berichteten mit größerer Wahrscheinlichkeit von erhöhten materiellen und Aufsichtsvernachlässigungen. Anbieter, die von einem erhöhten Frustrationsniveau innerhalb einer Familie berichteten, berichteten mit höherer Wahrscheinlichkeit auch über mehr Familienkonflikte und materielle Vernachlässigung in dieser Familie. Die Ergebnisse dieser Studie können in die strategische Entscheidungsfindung für Maßnahmen und Programme einfließen, die sich mit den Herausforderungen befassen, denen einkommensschwache Familien mit kleinen Kindern in Notsituationen ausgesetzt sind. 抄録: パンデミック時の子どもの虐待リスクの評価:家庭への導線としての遠隔医療による家庭訪問プログラムの利用 COVIDȀ19パンデミックは、多くの子どもの虐待リスク要因に影響を与え、脆弱な家族の虐待にも影響を与えている可能性がある。本研究では、エビデンスに基づいた家庭訪問プログラムであるSafeCare®の認定プロバイダー258名を対象に、彼らがサービスを提供している家族へのパンデミックの影響についての認識調査をした。この調査では, プロバイダーが担当している幼い子どもを持つ家族の子どもの虐待や家庭内の暴力のリスクが全体的に変化したと感じているかどうか, また変化の原因となった要因について調べた。回帰分析では, ソーシャルディスタンス, 感情的な葛藤, 公的資源やサービスへのアクセスに対する家族の能力についてのプロバイダーの評価と, 家庭内での子どもの虐待と家族の暴力のリスクに対するプロバイダーの認識との関係を推定した。その結果, 87％のプロバイダーが, パンデミックの間に虐待のリスクが高まったと考えていた。就業のために社会的な距離を取れない家族にサービスを提供しているプロバイダーは, サービスを提供している家族の間で育児監督上のネグレクトや物質的なネグレクトが増加したと報告する傾向にあった。また、家族が高まるフラストレーションに苦しんでいると報告した提供者は、提供する家族の間で、家族葛藤や物質的なネグレクトが増えたと報告した。本研究で得られた結果は、低所得で幼い子どもを持つ家族が緊急時に直面する問題に対処するための政策やプログラムの戦略的意思決定に役立つと考えられる。 摘要: COVID‐19大流行已经影响了许多虐待儿童的风险因素, 并可能影响弱势家庭中的虐待行为。我们调查了258位经过认证的循证家访计划"安全看护®"提供者, 了解他们对大流行带给其所服务家庭影响的看法。我们调查了提供者是否意识到他们所服务的有幼儿的家庭中虐待儿童和家庭暴力风险的总体变化, 以及可能导致变化的因素。回归分析估算了提供者对家庭社交距离、情感斗争和公共资源或服务获取能力的评估, 与提供者对家庭中虐待儿童和家庭暴力风险的感知之间的关系。调查结果表明, 87%的提供者认为大流行期间虐待风险增加了。为因就业而无法保持社交距离的家庭服务的提供者更有可能报告称, 在他们所服务的家庭中, 监管忽视和物质忽视有所增加。提供者报告说, 在他们所服务的家庭中, 受挫程度较高的家庭也报告了更多的家庭冲突和物质忽视。这项研究的结果可以为政策和方案的战略决策提供信息, 以解决有幼儿的低收入家庭在紧急情况下面临的挑战。 ملخص: تقييم مخاطر إساءة معاملة الأطفال أثناء جائحة كوفيد‐19: استخدام برنامج الرعاية الصحية عن بُعد للزيارة المنزلية كوسيلة للوصول إلى العائلات أثرت جائحة كوفيد‐19 على العديد من عوامل خطر سوء معاملة الأطفال وربما أثر على سوء المعاملة بين العائلات المعرضة للمخاطر. قامت الدراسة باستطلاع آراء 258 من مقدمي الخدمة المعتمدين لبرنامج الزيارات المنزلية المستند إلى الأدلة ((SafeCare® ، حول تصورهم لتأثير الوباء على العائلات التي يخدمونها. كما قمنا بفحص ما إذا كان مقدمو الخدمات قد لاحظوا حدوث تغيير بشكل عام في إساءة معاملة الأطفال ومخاطر العنف الأسري بين العائلات التي لديها أطفال صغار ، والعوامل التي ربما تكون قد ساهمت في التغييرات. أظهر تحليل الانحدار العلاقة بين تقييم مقدمي الخدمة لقدرة الأسر على التباعد الاجتماعي ، والصراعات العاطفية ، والوصول إلى الموارد / الخدمات العامة مع تصور مقدمي الرعاية لسوء معاملة الأطفال ومخاطر العنف الأسري في المنزل. تشير النتائج إلى أن 87 بالمائة من مقدمي الخدمات يعتقدون أن مخاطر سوء المعاملة قد زادت أثناء الوباء. كان مقدمو الخدمة الذين يخدمون الأسر التي لم تكن قادرة على التباعد لاجتماعي بسبب العمل أكثر عرضة للإبلاغ عن زيادة الإهمال الإشرافي والإهمال المادي بين العائلات التي يخدمونها. أفاد مقدمو الخدمات الذين قالوا إن العائلات كانت تواجه مستويات عالية من الإحباط عن وجود مزيد من الصراع الأسري والإهمال المادي بين العائلات التي يخدمونها. يمكن لنتائج هذا البحث أن تفيد عمليات صنع القرار الاستراتيجي للسياسات والبرامج التي تعالج التحديات التي تواجه الأسر منخفضة الدخل التي لديها أطفال صغار في حالات الطوارئ.